Le centre du monde : 2003-2008 : Un projet de Erwan Mahéo. - Mahéo, Erwan; Association R1 (s.l. : Association R1, 2009)
QS Serafijn ; Genod, Yves-Noël ; Delepeleire, Damien ; Durez, Anne ; Estève, Lionel ; Beaucarne, Boris ; Modé, Joâo ; Maire Duprat ; Reuzé, Sébastien ; Noiret-Thomé, Xavier ; Dinahet, Marcel ; Van der Eerden, Paul ; Arthuis, Isabelle ; Evrard, David ; Joly, Patrice
boek